Pathways through early childhood education in ethiopia, India, and Peru: rights, equity, and diversity - Woodhead, M (Palgrave Macmillan, 2012)
This chapter summarizes research within Young Lives into early childhood transitions,2 looking at children’s experiences within early childhood and primary education in three of the four Young Lives study countries. Numerous lines of research have converged to produce a compelling case for prioritizing early childhood care and education (ECCE) services. Research demonstrates that the earliest years of a child’s life are a crucial period of biological, neurological, psychological, social, and emotional growth and change; that poverty and other disadvantages can impact in numerous (and in some respects irreversible) ways on ‘developmental potential’ and that well-planned early interventions can have long-term positive outcomes for children. Economic analyses have shown that access to high-quality early childhood care and education is not only good for children’s development, it is also an important pro-poor strategy capable of increasing equity. It can also be cost-effective, with some well-designed programmes calculating high rates of return from early ‘investment in human capital’. Underlying all these persuasive lines of analysis is the principle on which all initiatives should be built — that young children have a right to development and to education in their best interests, without discrimination (summarized in Woodhead 2006; and Siraj-Blatchford and Woodhead 2009)